Aerodynamic Optimization Design of Duct Body Structure for Coaxial Rotor Unmanned Aerial Vehicles - Du Siliang; Zha Yi; Zhao Qijun (International Journal of Aerospace Engineering)
With the rapid development of vertical takeoff and landing aircraft, urban air traffic has gradually attracted people’s attention. The lift system is a key technology in the composition of vertical takeoff and landing aircraft systems. Due to its compact structure, low noise, safety, and reliability, the ducted lift body has been widely used as a thrust or lift device in aircraft design and has become one of the development directions for future electric vertical takeoff and landing aircraft. This article focuses on the aerodynamic optimization design of the main lift duct body components of a coaxial multirotor unmanned aerial vehicle, aiming to improve its power load and wind drag. The specific method is to remove the partial duct structure between the upper and lower coaxial rotors; change the flow characteristics of the flow field around the duct body; then establish a grid model of the duct body suitable for numerical analysis; analyze its aerodynamic characteristics in hovering, axial flow, and oblique flow states; and finally compare the aerodynamic characteristics with the unmodified duct body structure. The numerical simulation results show that the modified duct body has a significant increase in aerodynamic efficiency and a 4.5% increase in power load compared to the unmodified one. In order to further verify the flight performance of the modified ducted body structure of the drone, we designed and produced two ducted coaxial multirotor drones. Compared with the unmodified ducted body structure of the drone, the modified drone structure reduced weight by 800 g and increased flight time by 11.5%. The above methods have proven the effectiveness of optimizing the design of the duct body structure, providing a theoretical basis for the aerodynamic design and optimization of large duct vertical takeoff and landing aircraft.